Motor Control Center Breaker Modification Through On/Off Switch to Prevent Motor Failure - Ahmad Rosyiddin; Imam Maulana Arief; Novarino Herdyan Minanta (Journal of Mechanical Design and Testing, 2023)
Motor Control Center (MCC) GT module, is a power breaker device that connects the voltage source to the load. MCC breaker rack-in and rack-out activities can be classified as unsafe action and unsade condition.  Because there is a possibility of explosion. As it had happened several times in several places in the world. In 2021 there were 3 force derating and force outages which are caused by MCC motor breaker failures. That accident resulted 500,516.67 KWh loss or Rp 682,262,223,- ($ 44,766). Therefore, modifications need to be made to 0.4kV MCC breaker by adding a selector for the order off blocker to minimize socket damage due to frequent rack-in-rack-out breakers activity. After installing the modification to all breakers in Priok POMU, there was no failures occurred. The frequency of rack-in-rack-out activities were reduced significantly and that is a good result for operation safety. This modification can also prevent Priok POMU from a potential loss and potentially increase net profit up to Rp 221,549,398,- ($ 14,537).